Relación entre el aspecto visual, la densidad y la composición química del corcho - CÁCERES ESTEBAN, M. J.; GARCIA-VALLEJO, M. C.; GARCIA DE CECA, J. L.; GONZÁLEZ-ADRADOS, J. R. (V Congreso Forestal Español, 2009)
Este trabajo profundiza en el conocimiento de las propiedades del corcho, estudiando la relación entre las dos características principales desde el punto de vista físico (porosidad y densidad) y la composición química del material. Para ello se han tomado dos muestras de tapones naturales de cada una de las tres clases de calidad utilizadas por una industria seleccionada como representativa. Cada una de las dos muestras es de procedencia distinta: Andalucía y Cataluña. En cada tapón se ha determinado la porosidad lateral, la densidad, y la composición química según la metodología de análisis fraccionado clásico. Los resultados de los análisis de la varianza realizados muestran que la composición química del corcho es relativamente homogénea, y no se ve afectada, en general, por ninguno de los dos factores considerados: calidad y procedencia. La excepción es el contenido de suberina, en el que se encuentran porcentajes significativamente mayores para los corchos de mejor calidad que para los de las otras dos clases consideradas y para los procedentes de Cataluña respecto de los de Andalucía. El estudio de las correlaciones entre las variables estudiadas muestra la relación existente entre la presencia de componentes no estructurales (extractivos) y la porosidad, lo que sugiere que la mayor parte de estos compuestos se localizan en los canales lenticulares, y son responsables, además del aumento de la densidad del material.
The following values have no corresponding Zotero field: periodical: V Congreso Forestal Español pub-location: Avila
Keywords: calidad industrial; polifenoles; Porosidad; suberina

Variability of suberin composition of reproduction cork from Quercus suber throughout industrial processing - Conde, E.; GARCIA-VALLEJO, M. C.; Cadahia, E. (HOLZFORSCHUNG, 1999)
The chemical composition of suberin was studied in cork planks fromthree different trees of Spanish Quercus suber at four different stages of the industrial processing of first transformation: stripping (a), first rest (b), boiling followed by open air rest (c1) and boiling followed by store-room rest (c2). The monomeric composition was determined by gas chromatography/mass spectrometry in the product of depolymerization of the free of extractives cork with sodium methoxide-methanol. The average concentrations of the main monomers were: 1-alkanols (C-20-C-26) 4.17 %; alkanoic acids (C-20-C-26) 5.99 %; alpha, omega-alkanedioic acids (C-16-C-24) 6.20 %; omega-hydroxy-alkanoic acids (C-20-C-26) 29.41 %; erythro- and threo-9, 10-dihydroxyoctadecanedioic acids 6.76 %, erythro- and threo-9,10,18-trihydroxyoctadecanoic acids 9.50 %, 9,10-epoxy-18-hydroxyoctadecanoic acid 2.72 % and 9,10-epoxy-octadecanedioic acid 2.93 % and ferulic acid 5.05 %. Significant differences were observed between samples taken at the stripping and after boiling with store room rest, and both groups of samples differed from those picked after the other two processing stages. Ten components were selected as providing the greatest discrimination among stages: 9-octadecenedioic, 18-hydroxy-9-octadecenoic, eicosanedioic and 9,10-epoxy-18-hydroxy-octadecanoic acids, tetracosanol, and five unidentified components.
The following values have no corresponding Zotero field: pub-location: GENTHINER STRASSE 13, D-10785 BERLIN, GERMANY publisher: WALTER DE GRUYTER & CO
Keywords: Quercus suber; suberin; cork; industrial processin

Waxes composition of Quercus suber reproduction cork from different Spanish provenances - Conde, E.; GARCIA-VALLEJO, M. C.; Cadahia, E. (Wood Science and Technology, 1999)
The chemical composition of waxes was studied in Quercus suber cork planks collected in seven localities of the three main production areas of Spain. Waxes were extracted with chloroform (CHCl3 ) and the extract was submitted to saponi®cation in order to obtain the neutral and acid fractions. The trimethylsilyl derivatives of both fractions were analysed by GC-MS. The seven populations cannot be distinguished by their total contents of waxes (Chloroform extract) and of the neutral and acid fraction. This lack of differences could be due to the important variability among samples of each population. The neutral fraction was mainly composed of fatty alcohols (all the even members from C18 to C26 , with traces of the intermediate odd members and some unsaturated groups) and triterpenes (11 components, among them friedelin, betulin and cerin were identi®ed) and a very small amount of monocarboxylic fatty acids (C16 and C24 members) was also present. The main group of compo- nents of the acid fraction was that of fatty acids (saturated even C14±C24 and odd C15 , C17 , C21 members, accompanied by a great amount of unsaturated terms and some x-hydroxyacids, 18-hydroxy-9,12-octadecadienoic and 18-hydroxy-9-oct- adecenoic acids). Four triterpenes and the C20 and C24 alcohols were also detected in the acid fraction. Signi®cant differences were found among the corks of the various provenances in the global contents of alcohols and triterpenes and in these individual components contents of the neutral fraction. Concerning the differences among the various provenances in the contents of the groups of fatty acids, alcohols, and triterpenes in the acid fraction, a higher number of differ- ences were obtained in the comparisons of the contents of acids and triterpenes, whereas the differences were practically null in the case of the alcohols. When the differences were studied considering the individual compounds, the relation with the behaviour of the contents of the groups of components was not as clear as it happens in the neutral fraction. In this case, the differences were scarcer and they did not show a unique pattern, neither in the components, nor the populations. There is no correspondence in the differences among the provenances regarding the components of the neutral fraction or those of the acid fraction. No clear relationship was found between the geographical proximity of the provenances and chemical similarity of the waxes composition.
Keywords: Acid fraction; component (voyant); Cork; neutral fraction; provenance; waxes

Waxes composition of reproduction cork from Quercus suber and its variability throughout the industrial processing - Conde, E.; GARCIA-VALLEJO, M. C.; Cadahia, E. (Wood Science and Technology, 1999)
The chemical composition of waxes was studied in cork planks from three different trees of Spanish Quercus suber at four different stages of the in- dustrial processing of the ®rst transformation: stripping, ®rst rest, boiling fol- lowed by open air rest and boiling followed by store-room rest. Waxes were extracted with chloroform (CHCl3 ) and the extract was submitted to saponi®cation in order to obtain the neutral and acid fractions. The trimethylsilyl derivatives of both fractions were analysed by GC-MS. An important decrease of the total content of waxes -CHCl3 extract-(average values: 10.13 to 4.91%) and of the acid fraction (average values: 2.51 to 0.96%) was observed throughout the industrial processing. Some differences were also found among trees, two of them being richer in total waxes (average, 8.14 and 7.71%) than the other one (average, 4.67%). Concerning the three groups of identi®ed components (fatty acids, fatty alcohols and triterpenes), the contents of the fatty alcohols and acids suffer an important reduction during the ®rst rest (average values: 30.39 to 17.53% and 58.73 to 31.48%, respectively), while after boiling, there is a decrease of the triterpenes concentrations (79.16 to 58.00% -neutral fraction- and 40.23 to 23.20% -acid fraction-), being greater when the second rest is carried out in a store room. Signi®cant differences among trees were only found in the fatty alcohols contents. The neutral fraction was mainly composed by fatty alcohols (all the even members from C18 to C26 , with traces of intermediate odd members and some unsaturated groups, C20 and C21 ) and triterpenes (14 components, among them friedelin, betulin and cerin were identi®ed), and a very small amount of monocarboxylic fatty acids (C16 , C18 , C22 and C24 members) was also present. The main group of components of the acid fraction was that of fatty acids (saturated even C12±C24 and odd C15 , C17 , C21 members, accompanied by a great amount of unsaturated terms and some x-hydroxyacids, 18-hydroxy-9,12-octadecadienoic and 18-hydroxy-9-octadecenoic acids). Four triterpenes, the C20 , C24 and C28 alcohols and ferulic acid were also detected in the acid fraction. Some of these individual components of each fraction were also affected by the industrial processing and presented signi®cant differences among the studied trees.
Keywords: Acid fraction; component (voyant); Cork; indutrial processing stage; neutral fraction; waxes